Sports‐related eye and adnexal injuries in the Western Australian paediatric population. (9th December 2015) - Hoskin, Annette K.; Yardley, Anne‐Marie E.; Hanman, Kate; Lam, Geoffrey; Mackey, David A.
Abstract: Purpose: To identify the causes of sports‐related eye and adnexal injuries in children in Perth, Western Australia, to determine which sporting activities pose the highest risk of eye and adnexal injury to children. Methods: We performed a 12‐year retrospective review of children admitted to hospital from 2002 to 2013 with sports‐related ocular and adnexal eye injuries. The main outcome measures were the cause and type of ocular and adnexal injuries, age and gender risk factors. Results: A total of 93 cases of sports‐related ocular and adnexal injury were identified in the 12‐year time period. A peak in injuries occurred for 12‐ to 14‐year‐olds with a second peak in 6‐ to 8‐year‐olds; the median age was 8.82 years (range = 1.59–16.47). Cycling, football (including soccer and Australian Rules Football), tennis, trampolining, fishing and swimming were the sports responsible for the greatest number of injuries, a total of 63%. More than one‐third (35%) of injuries resulted from being struck by a blunt object, and more than a quarter (26%) were as a result of contact with a blunt projectile. Conclusion: Serious ocular and adnexal injuries have occurred in children as a result of participating in sports, with cycling and football being the largest contributors in the 12‐year period we assessed. As we continue to encourage children to spend more time participating in sports and recreational activities, identifying associated risk factors will help us develop injury prevention strategies to promote eye safety for children.